Myoelectric signs of fatigue and force failure during endured isometric contractions in elderly - Rosponi, A.; Felici, F.; Bazzucchi, I.; Sbriccoli, P.; Fattorini, L.; Filligoi, G. C. (International Journal of Computer Science in Sport, 2002)
Age-related muscle morphological alterations are associated to changes in the motor units' (MU) control properties, to a decrease in maximal isometric torque and to an higher resistance to fatigue. This study is aimed at investigating how these age-related physiological modifications are reflected by peculiar signs of myoelectric fatigue and/or changes in the deterministic content of the surface electromyographic signal (sEMG). For this purpose the sEMG was analysed in time and frequency domains using as global indexes of myoelectric fatigue the sEMG Root Mean Square (RMS), average conduction velocity (CV) and the Median Frequency (MDF). Concerning the non-linear approach, the recurrence quantification analysis (RQA) was applied, and one of its parameters, the percent of determinism (%DET), was computed. Besides, we also sought to test if the above indicators correlate with the ultimate end-point (endurance time, ET) for the task.